2018
DOI: 10.1063/1.5050631
|View full text |Cite
|
Sign up to set email alerts
|

The effect of multidirectional bias magnetic fields on the converse magnetoelectric response of multiferroic concentric composite ring

Abstract: A composite multiferroic ring was characterized under two orthogonal bias magnetic fields while electrically loaded near resonance to measure the circumferential converse magnetoelectric (CME) response. The composite multiferroic structure consisted of an inner magnetostrictive Terfenol-D ring with an axially aligned preferred magnetocrystalline axis bonded to a radially polarized outer piezoelectric poled lead zirconate titanate ring to form a concentric ring structure. A single uniform bias magnetic field wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…Second, the experimental results were found to be in an excellent agreement with the numerical nodal displacement resulting from the bonding contact boundary condition. The latter closely resembles the physical contact boundary conditions observed in the experiment since the cylinders were bonded using silver epoxy (Chavez et al, 2016;Newacheck et al, 2018), hence preventing the relative movement at the interface diameter. Since the frequency resolution of the experiment was coarser than that reported in the computational data, Gaussian approximation was used to refine the resolution and yielding an experimental resonance peak at 30.875 kHz, which compares very well to the numerically calculated resonance frequency of 31.185 kHz, that is, less than 1% difference.…”
Section: Harmonic Resultsmentioning
confidence: 53%
“…Second, the experimental results were found to be in an excellent agreement with the numerical nodal displacement resulting from the bonding contact boundary condition. The latter closely resembles the physical contact boundary conditions observed in the experiment since the cylinders were bonded using silver epoxy (Chavez et al, 2016;Newacheck et al, 2018), hence preventing the relative movement at the interface diameter. Since the frequency resolution of the experiment was coarser than that reported in the computational data, Gaussian approximation was used to refine the resolution and yielding an experimental resonance peak at 30.875 kHz, which compares very well to the numerically calculated resonance frequency of 31.185 kHz, that is, less than 1% difference.…”
Section: Harmonic Resultsmentioning
confidence: 53%
“…Finally, the vibrational displacements were induced by subjecting the piezoelectric cylinder to a radial AC electric field (30 kHz) using a waveform generator (Agilent 33210A) and a high voltage amplifier (Trek PZD700A) at a level of 20 kV/m. The selection of the amplitude and frequency of the electric field was based on previous studies reported in Newacheck et al (2018), Chavez et al (2016) and Youssef et al (2017a).…”
Section: Experimental Approachmentioning
confidence: 99%
“…Analytical models predict the concentric cylinder geometry to exhibit a giant magnetoelectric response due to the curvature enhancing the strain transfer between material layers (Wang et al 2010a). Our group has extensively studied the CME response of the concentric cylinder structure using experimental, analytical, and computational analyses (Newacheck et al 2018;Chavez et al 2016;Youssef et al 2020a). Specifically, we have experimentally investigated the effect of the bias magnetic field direction, electric field direction, and bonding methods, while analytically explored the effect of mechanical boundary conditions, and developed validated computational models (Newacheck et al 2018;Chavez et al 2016;Youssef et al 2020a, b).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the components have important electrical, magnetic, optical, and photochemical applications . Bi‐based compounds have drawn a lot of attention because for their potential application as novel photocatalysts, in which the lone pair electrons of Bi 3+ ere are often found to possess hybridized band structures . Especially, Aurivillius compounds have been widely reported because of its special layer perovskite atom arrangements and favourable optical band structure .…”
Section: Introductionmentioning
confidence: 99%